2020
DOI: 10.3389/fpls.2020.00776
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs Containing Resistance Genes for Sclerotinia Stem Rot in Brassica napus Using Comparative Transcriptomic Studies

Abstract: Sclerotinia stem rot is a major disease in Brassica napus that causes yield losses of 10-20% and reaching 80% in severely infected fields. SSR not only causes yield reduction but also causes low oil quality by reducing fatty acid content. There is a need to identify resistant genetic sources with functional significance for the breeding of SSR-resistant cultivars. In this study, we identified 17 QTLs involved in SSR resistance in three different seasons using SNP markers and disease lesion development after ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 55 publications
10
27
0
Order By: Relevance
“…RNA-seq analysis can quickly identify differently expressed genes (DEGs) between different samples. Up to now, RNA-seq has facilitated the identification of DEGs in rapeseed under abiotic stresses such as drought [ 5 ], freezing [ 6 ] and salinity [ 7 ], as well as some candidate genes related to sclerotinia [ 8 ], seed aging [ 9 ], seed coat color [ 10 ], and flowering time [ 11 ]. Some studies on herbicide stress to plants were also carried out using RNA-seq.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq analysis can quickly identify differently expressed genes (DEGs) between different samples. Up to now, RNA-seq has facilitated the identification of DEGs in rapeseed under abiotic stresses such as drought [ 5 ], freezing [ 6 ] and salinity [ 7 ], as well as some candidate genes related to sclerotinia [ 8 ], seed aging [ 9 ], seed coat color [ 10 ], and flowering time [ 11 ]. Some studies on herbicide stress to plants were also carried out using RNA-seq.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that all QTLs worked cumulatively for disease and the lines having all three QTLs showed the highest resistant level. Qasim et al (2020) identified three major QTLs through comparative transcriptomic studies harboring 36 putative candidate genes from resistant B. napus lines that might actively involved in SSR resistance. Wu et al (2013) identified 10 and 3 QTLs for stem and leaf resistance in B. napus , respectively.…”
Section: Resistance Sources For Major Pathogensmentioning
confidence: 99%
“…In another study, the exaptation of a transposable element (TE) enabled a duplicated iron-stress gene (CYP82C2) to function in plant defence biosynthetic pathways (Barco et al 2019). Crosstalk between biotic and abiotic response pathways has been reported in Brassica-pathosystems, including blackleg (Tortosa et al 2019;Qasim et al 2020) and it is tempting to speculate that common genes in these pathways might have undergone exaptation to function from one stress condition to another. Gene exaptation presents an interesting view of how QR may have evolved in response to pathogen pressure.…”
Section: Exaptation Of Gene Function As a Mechanism For Durable Resistancementioning
confidence: 99%